2015
DOI: 10.1155/2015/463703
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration ofGanoderma lucidumto Lead-Exposed Rats Protects Erythrocytes against Hemolysis: Implicates to Anti-Anemia

Abstract: We studied the effect of chronic oral exposure to lead acetate (PbA) on the sensitivity of RBC to hemolysis and whether the sensitivity could be decreased by feeding the rats with extract of medicinal mushroom Ganoderma lucidum. Three groups of rats, control, PbA-exposed, and G. lucidum (Gl)+PbA, were used. PbA (3 mM) was administered via drinking water and G. lucidum extract by gavage at 300 mg/Kg BW/day for 12 weeks. Afterwards, the rats were killed and washed RBCs were subjected to hemolysis in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Pb can increase thrombin generation and accelerating the coagulation process by tissue factor in plasma. Pb interferes with normal red blood cell formation by inhibiting important enzymes, inhibits SOD and reduces glutathione levels, increasing erythrocyte vulnerability to oxidative stress (34). In association with DVTs, Pb decreases the plasminogen activator antigen (t-PA:Ag), increasing the production of this inhibitor (PAI-1).…”
Section: Discussionmentioning
confidence: 99%
“…Pb can increase thrombin generation and accelerating the coagulation process by tissue factor in plasma. Pb interferes with normal red blood cell formation by inhibiting important enzymes, inhibits SOD and reduces glutathione levels, increasing erythrocyte vulnerability to oxidative stress (34). In association with DVTs, Pb decreases the plasminogen activator antigen (t-PA:Ag), increasing the production of this inhibitor (PAI-1).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, there was no apparent clinical signs of toxicity observed in both acute and sub acute studies when the extract was orally administered, however, it was observed that feed and water consumption increase within the period of study, thus causing an increase in body weights of experimental rats. This may be due to increase in metabolism and anti oxidant effect of the extract as reported by Oluba et al [22][23][24] while other reports indicate decrease in weight [25].…”
Section: Discussionmentioning
confidence: 90%
“…These include differential effects on the inhibition of eukaryotic DNA polymerases, thromboxane A2-signaling pathways in human platelets, inhibition of tumor invasion in vitro and in vivo, cytotoxicity to several cancer cells in vitro, anti-human immunodeficiency virus-1 protease activity and regulation of osteoclastogenesis [14]. The other pharmacological properties of triterpenoids were reported such as, antihypertensive [30], antianemia [31], cardioprotective [32,33], antifibrotic effect [34,35], anti-oxidant [36], anti-HIV-1 activity [37] and anticancer [38,39].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%